2005
DOI: 10.1016/j.jacc.2004.12.082
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcomes After Coronary Stenting Versus Bypass Surgery for the Treatment of Multivessel Disease

Abstract: At five years there was no difference in mortality between stenting and surgery for multivessel disease. Furthermore, the incidence of stroke or myocardial infarction was not significantly different between the two groups. However, overall MACCE was higher in the stent group, driven by the increased need for repeat revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 545 publications
(48 citation statements)
references
References 10 publications
5
39
3
1
Order By: Relevance
“…The BARI trial results are consistent with those of recent clinical trials such as ARTS (Arterial Revascularization Therapies Study) (12), which reported comparable 5-year mortality for coronary bare-metal stenting and CABG (8.0% stents vs. 7.6% CABG), but more subsequent revascularization (30.3% vs. 8.8%) and more angina (21.2% vs. 15.5%) in the stenting group. Metaanalyses (13) and registries (14) based on larger and more diverse populations have shown small but statistically significant survival advantages with CABG at 3 to 5 years.…”
Section: Discussionsupporting
confidence: 84%
“…The BARI trial results are consistent with those of recent clinical trials such as ARTS (Arterial Revascularization Therapies Study) (12), which reported comparable 5-year mortality for coronary bare-metal stenting and CABG (8.0% stents vs. 7.6% CABG), but more subsequent revascularization (30.3% vs. 8.8%) and more angina (21.2% vs. 15.5%) in the stenting group. Metaanalyses (13) and registries (14) based on larger and more diverse populations have shown small but statistically significant survival advantages with CABG at 3 to 5 years.…”
Section: Discussionsupporting
confidence: 84%
“…Thus patients underwent concomitant treatment of multiple vessels during the same hospitalization. The good results in the present series are to be noted in the case of complete revascularization in patients with multivessel coronary artery disease, compared to results reported for surgery or PCI alone [19,20,21]. Compared to other hybrid revascularization series involving right coronary stenting [22,23,24], our follow-up results were very satisfactory.…”
Section: Discussionsupporting
confidence: 60%
“…The same results were observed in the Arterial Revascularization Therapies Study (ARTS), which compared bare metal stenting with CABG, even though the mortality rates in the PCI group were smaller (8%) than those in the MASS II PCI group. 12 This difference in the PCI group could be due to the more serious clinical characteristics of our population, with a higher incidence of risk factors and a higher incidence of triple-vessel disease, with 93% of proximal left anterior descending coronary artery involvement, compared with the ARTS population (58% and 30%, respectively). Furthermore, in ARTS, the major adverse cardiac events were higher in the stent group, driven by the increased need for additional revascularization; similar results were found in MASS II.…”
Section: Discussionmentioning
confidence: 82%